Legal Liability Company Based On Sharing Economy to Service And Consumer Providers - Fakhry Amin (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
administrative accountability. In addition, the company sharing economy is given the flexibility to resolve the issue with the providers that are not regulated in the law as a form of enforcement of good corporate principles. The status of the company based on the sharing economy in Indonesia is not clearly regulated in UUPT due to the involvement of the 3rd party. However, it does not mean that the sharing economy company is not accepted in Indonesia where the government keeps granting a business license to the quo company with the quo company's record given the legal basis to further spur national development arranged as a joint effort based on the principle of kinship.